Utilization of nanomaterials functionalized bio-field-effect transistors for detection of cancer biomarkers - Keerthana Madhivanan; Raji Atchudan; Sandeep Arya; Ashok K. Sundramoorthy (Oral Oncology Reports)
After the outbreak of the coronavirus disease (COVID-19), bio-sensing devices became very essential life-saving tools and showed a different perspective in the medical diagnostic field. Despite of all the advanced treatments in cancer, the early detection and diagnosing the first stage of the disease is very important. Over the last decade, the field-effect transistors (FETs) based biosensors have been demonstrated for the detection of various cancer biomarkers. FETs based biosensors were highly sensitive and selective compared to the other traditional sensing devices such as amplification-refractory mutations, Western blot, electrochemical, digital polymerase chain reaction and next generation sequencing methods. Moreover, FETs-based biosensors offer the early diagnosis of the disease with high specificity and high sensitivity at a relatively low cost.